Agglomeration and Dispersion Forces in the Riyadh Region: A Spatial Economic Analysis of Unbalanced Growth and Over-Urbanization (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study presents a spatial economic analysis of the phenomenon of unbalanced growth in the Riyadh Region through an examination of the interplay between agglomeration forces that attract economic activities and population concentration toward the capital city and dispersion forces resulting from the pressures of rapid urban growth. The study reviews the geographic and demographic characteristics and the diversified economic structure of the Riyadh Region and analyzes its comparative advantages, including local market demand, human capital resources, strategic geographic location, and topographical features, in addition to its contribution to Saudi Arabia’s gross domestic product (GDP). It also examines unemployment rates, average income levels, domestic and foreign direct investment (FDI), the spatial distribution of economic activities, internal migration patterns, infrastructure development, and the degree of economic concentration. The analysis is grounded in major regional economic theories, particularly Perroux’s Growth Pole Theory, Krugman’s Core–Periphery Model, Myrdal’s Theory of Circular and Cumulative Causation, and Christaller’s Central Place Theory. The findings indicate that agglomeration forces continue to outweigh dispersion forces despite the emergence of urban diseconomies, such as rising housing costs and increasing traffic congestion. The study concludes by proposing a set of development policies aimed at managing economic concentration spatially and linking it to the objectives of Saudi Vision 2030, thereby transforming Riyadh’s centrality into a driver of balanced regional development rather than a self-reinforcing model of economic concentration.
Keywords: Spatial Economic Concentration; Unbalanced Growth; Growth Pole Theory; Core–Periphery Model; Circular and Cumulative Causation; Comparative Advantage; Internal Migration; Saudi Vision 2030; Foreign Direct Investment; Riyadh Region